Tecnologias educacionais na micropolítica do trabalho vivo na atenção domiciliar - Francisca das Chagas Cunha Gonçalves Neta (2017)
This research starts from the premise that the potentiality of home care favors the centrality in the living work in act by increasing the inventive and creative capacity of the professionals. These, in creating escape lines, have the possibility of causing ruptures in the normative logic of the hegemonic model, escaping from the pragmatic and operating in heterogeneity using educational technologies. The general objective of this research was to analyze the use of educational technologies in the micropolitics of live work at home care act. Complementary to this, we also sought to identify how educational technologies are used in the production of home care and describe how these technologies subsidize the educational processes in the territory of home care. We chose a qualitative research with a cartographic approach because it allows us to capture movements, to approach and observe phenomena that express intentions, disputes and desires intensively investigated. This cartographic investigation is anchored in the Post-Structuralist perspective of the cartographic guides Deleuze and Guattari, which allowed the researcher to project a new look on health work, the intersection of the use of educational technologies and the production of care in home care in their subjectivity. The territory of this investigation was a Home Care Service, Better at Home Program, in the city of Betim - Minas Gerais. To capture the movements of production and use of educational technologies, a home care team was chosen, defined in this research, as a guide team. The effects of the cartographic trip were presented through narratives that express the micropolitics of the living work of each participant of the guide team. From this initial analytical process, two empirical categories were constructed, being first with two subcategories. Data analysis revealed that the creation/ production and utilization movements of educational technologies take place in the micropolitics of living labor in the home care act, and these technologies to (de) territorialize the hard and normative fields of knowledge can (re) territorialize in different Velocities and intensities in a trajectory of escape routes, triggering know-how, which in connection with other agencies can engender the multiplicities of educational processes in the molecular level of home care management.hese movements of escape lines of professionals, reinvent the educational process from the singularity experienced in the territory of home care seeking, in repetition, the difference of creative doing at home. With this, the new ways of teaching and learning, through educational technologies, emerge cracks in the educator-educating duality, revealing educational processes that do not close in on itself and thus open itself to the new, re-meaning learning in the territory of home care. Educational technologies are incorporated into home-based care, although printed, dialogic and expository modalities are still restricted. Thus, although educational technology is a means of triggering and enhancing the production of care, it is still a challenge to think rhythmically about the educational reality in the micropolitical plan of home care under the Unified Health System.